Arterial blood gas levels in high altitude Kashmiri population, India - Sayeed, Sheikh Imran; Handoo, Shazia; Wani, Hilal Ahmad; Walvir, Nazia Manzoor; Danish, Qazi; Pampori, Rafiq Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: The valley of Kashmir lies at an average height of 1730 m above the sea level with a barometric pressure of 624 mmHg. The fall in atmospheric pressure at higher altitude decreases the partial pressure of inspired oxygen and hence the driving pressure for gas exchange in the lungs. At sea level the normal range of PaCO2 is 35 mmHg to 45 mmHg and at 1500m above sea level (barometric pressure 634 mmHg), the predicted normal PaO2 in a healthy young adult is approximately 80 mmHg; this contrasts with a value close to 95 mmHg at sea level. On these grounds this study was undertaken to formulate normal ABG values for this place as it lies at a higher altitude. Methods: The study was undertaken to measure "arterial blood gases" (ABG) in ethnic Kashmiri population and consisted of a sample of one hundred healthy Kashmiri subjects of either sex after proper inclusion and exclusion by spirometrically measuring Vital Capacity and Forced expiratory volume in one second/Forced vital capacity (Fev1/FVC). A modified Allen's test was performed to check for adequate collateral circulation ruling out Ischemia. Results: The average mean PaO2 of 78.51 ± 4.40 mmHg and the average mean PaCO2 of 33.37 ± 2.38 mmHg was obtained of the volunteers of both the sexes. The average mean pH of males (7.43 ± 0.02) was significantly lower than the mean pH of females (7.45 ± 0.021). Conclusions: The present study might provide useful base line normal values of Arterial Blood Gases for the local population and will be beneficial to the clinicians.